The analysis of the attention levels of individuals playing golf - Ahmet Tunc; Gulsum Bastug; Mehibe Akandere (Türk Spor ve Egzersiz Dergisi)
The purpose of this study is to investigate whether the golf exercises affect the attention level of the individuals in 14-15 years of age. The sample group of the study is occurring 60 students in 14-15 age group from Hekimoglu Vocational High School located in Selcuklu District of Konya. The mean age of the subjects participating in the study as the experimental group is 14.80 ± 1.38 years, mean age of the control group is 14.90 ± 1.39 years. Before and after the 8 weeks process Bourdon (1955) attention test is applied. SPSS 16.0 programme is used in evaluation and using the calculated values. The test of the data distribution is normal or not made by One-sample Kolmogorov-Smirnov test method and fixed that data have normal distribution. For the pre-test – posttest comparisons in the group paired samples t-test is used. As a result, in the survey made for inspecting the attention levels of the individuals in 14 – 15 age group who are making golf exercises, it is fixed that the golf exercise applied to the test group affects the attention level of the kids significantly. In this context, we can say that the golf exercise positively affect the attention properties of the kids in 14-15 age group.